Theories of change for tracking climate change adaptation. A quick reference guide - Jones, Kristal; Nowak, Andreea C.; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This document provides a quick reference guide on using theories of change in monitoring and evaluating adaptation to climate change. The reflections are based on learnings from applying climate adaptation M&E tools in different investment contexts (subnational, national). The notes provide definitions and explanations of key elements to consider in theory of change design and review and provide annotated collections of useful resources for deep dives. We illustrate the practical application of ToCs through case studies from Zambia and Ethiopia. The document is relevant for actors engaged in any adaptation cycle, from planning and implementation, to monitoring, evaluation, and reporting.